Paving the Rho in cancer metastasis: Rho GTPases and beyond - Jansen, Sepp R.; Wieland, Thomas (Pharmacology & therapeutics, 2018)
Malignant carcinomas are often characterized by metastasis, the movement of carcinoma cells from a primary site to colonize distant organs. For metastasis to occur, carcinoma cells first must adopt a pro-migratory phenotype and move through the surrounding stroma towards a blood or lymphatic vessel. Currently, there are very limited possibilities to target these processes therapeutically. The family of Rho GTPases is an ubiquitously expressed division of GTP-binding proteins involved in the regulation of cytoskeletal dynamics and intracellular signaling. The best characterized members of the Rho family GTPases are RhoA, Rac1 and Cdc42. Abnormalities in Rho GTPase function have major consequences for cancer progression. Rho GTPase activation is driven by cell surface receptors that activate GTP exchange factors (GEFs) and GTPase-activating proteins (GAPs). In this review, we summarize our current knowledge on Rho GTPase function in the regulation of metastasis. We will focus on key discoveries in the regulation of epithelial-mesenchymal-transition (EMT), cell-cell junctions, formation of membrane protrusions, plasticity of cell migration and adaptation to a hypoxic environment. In addition, we will emphasize on crosstalk between Rho GTPase family members and other important oncogenic pathways, such as cyclic AMP-mediated signaling, canonical Wnt/β-catenin, Yes-associated protein (YAP) and hypoxia inducible factor 1α (Hif1α) and provide an overview of the advancements and challenges in developing pharmacological tools to target Rho GTPase and the aforementioned crosstalk in the context of cancer therapeutics